Reply letter to "response to article by Johnna Perdrizet et al." by Gomez and colleagues. Issue 1 (31st December 2022) - Perdrizet, Johnna; Santana, Carlos Felipe S.; Senna, Thais; Alexandre, Rodrigo Fernandes; Sini de Almeida, Rodrigo; Spinardi, Julia; Wasserman, Matt
ABSTRACT: This communication seeks to address the questions and criticisms issued by Gomez and colleagues in their letter on our original study "Cost-effectiveness analysis of replacing the 10-valent pneumococcal conjugate vaccine (PCV10) with the 13-valent pneumococcal conjugate vaccine (PCV13) in Brazil infants." Gomez and colleagues are concerned that the assumptions used in our model may have unintended negative impacts for Brazil decision-making and we intend to clarify any potential misinterpretation of our assessment.